The accuracy and completeness for receipt of colorectal cancer care using Veterans Health Administration administrative data. Issue 1 (December 2016) - Sherer, Eric; Fisher, Deborah; Barnd, Jeffrey; Jackson, George; Provenzale, Dawn; Haggstrom, David
Abstract Background The National Comprehensive Cancer Network and the American Society of Clinical Oncology have established guidelines for the treatment and surveillance of colorectal cancer (CRC), respectively. Considering these guidelines, an accurate and efficient method is needed to measure receipt of care. Methods The accuracy and completeness of Veterans Health Administration (VA) administrative data were assessed by comparing them with data manually abstracted during the Colorectal Cancer Care Collaborative (C4) quality improvement initiative for 618 patients with stage I-III CRC. Results The VA administrative data contained gender, marital, and birth information for all patients but race information was missing for 62.1 % of patients. The percent agreement for demographic variables ranged from 98.1–100 %. The kappa statistic for receipt of treatments ranged from 0.21 to 0.60 and there was a 96.9 % agreement for the date of surgical resection. The percentage of post-diagnosis surveillance events in C4 also in VA administrative data were 76.0 % for colonoscopy, 84.6 % for physician visit, and 26.3 % for carcinoembryonic antigen (CEA) test. Conclusions VA administrative data are accurate and complete for non-race demographic variables, receipt of CRC treatment, colonoscopy, and physician visits; but alternative data sources may be necessary to capture patient race and receipt of CEA tests.